PENYULUHAN PENGENALAN HAMA DAN PENYAKIT TANAMAN PISANG SERTA CARA PENGENDALIANNYA DI DESA MOREKAU - Patty, John Alfred (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Hein Namotemo, 2024)
This service activity aims to provide practical skills and knowledge to the community about recognizing the types of pests and diseases of banana plants. The target of implementing this activity is the community of Morekau Village, West Seram District, West Seram Regency. Community participation in this activity was very good. This is related to the problems faced in banana planting, namely the main pests and diseases of banana plants which cause losses, both in quantity and quality. There was a positive response from the extension participants to continue effective and efficient control techniques, in order to minimize control costs and increase farmers' knowledge in the banana cultivation business. Therefore, farmers really need information regarding the main types of pests and diseases of banana plants and their control techniques